PENGARUH MANAJEMEN PENGETAHUAN DAN ORIENTASI TEKNOLOGI TERHADAP KAPABILITAS INOVASI SERTA IMPLIKASINYA TERHADAP KINERJA UMKM BERORINETASI HALAL - Fitriyani, Ika; Nana Sucihati, Roos; Sutanty, Marisa; Aurelia Kamal, Afina (Penerbit Lafadz Jaya, 2025)
His study examines the effects of knowledge management and technology orientation on innovation capability and their implications for the performance of halal-oriented micro, small, and medium enterprises (MSMEs). The growing demand for halal products has encouraged MSMEs not only to comply with regulatory and certification standards but also to enhance their innovative capacity in order to remain competitive in an increasingly dynamic market. Knowledge management plays a crucial role in the creation, storage, and application of information as a foundation for strategic decision-making and the development of new ideas. In parallel, technology orientation reflects the extent to which MSMEs adopt and utilize digital technologies to support and improve business processes. This study employs a quantitative approach by distributing structured questionnaires to 100 food and beverage MSME owners who have obtained halal certification or are currently in the certification process. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings indicate that knowledge management and technology orientation have a positive and statistically significant effect on innovation capability. Furthermore, innovation capability significantly influences the performance of halal-oriented MSMEs and mediates the relationship between knowledge management and technology orientation and MSME performance. These results highlight that effective knowledge management and comprehensive technology utilization are critical drivers of innovation and business performance among halal-oriented MSMEs.